El control quimico de plagas de frijol - Hallman, G (United Nations Development Programme, 1985)
A description is given of the different manners in which insecticide toxicity is expressed (lethal dose, continuous dose, lethal time, lethal concn., and effective dose), insect resistance to chemicals, insecticide types, application, and the role of chemical control in integrated pest control. Insect pests of beans in Latin America are listed. (CIAT)